Genetic and epigenetic risks of assisted reproduction. (October 2017) - Jiang, Ziru; Wang, Yinyu; Lin, Jing; Xu, Jingjing; Ding, Guolian; Huang, Hefeng
Abstract : Assisted reproductive technology (ART) is used primarily for infertility treatments to achieve pregnancy and involves procedures such as in vitro fertilization (IVF), intracytoplasmic sperm injection (ICSI), and cryopreservation. Moreover, preimplantation genetic diagnosis (PGD) of ART is used in couples for genetic reasons. In ART treatments, gametes and zygotes are exposed to a series of non-physiological processes and culture media. Although the majority of children born with this treatment are healthy, some concerns remain regarding the safety of this technology. Animal studies and follow-up studies of ART-borne children suggested that ART was associated with an increased incidence of genetic, physical, or developmental abnormalities, although there are also observations that contradict these findings. As IVF, ICSI, frozen-thawed embryo transfer, and PGD manipulate gametes and embryo at a time that is important for reprogramming, they may affect epigenetic stability, leading to gamete/embryo origins of adult diseases. In fact, ART offspring have been reported to have an increased risk of gamete/embryo origins of adult diseases, such as early-onset diabetes, cardiovascular disease, and so on. In this review, we will discuss evidence related to genetic, especially epigenetic, risks of assisted reproduction. Highlights: During ART treatment, gametes and embryos are exposed to non-physiological processes. The short- and long-term safety of assisted reproduction is of concern. There is an increased incidence of genetic and epigenetic risks in ART offspring. The exact mechanisms during the ART procedure need to be further investigated for its optimization.